Early Cenozoic Eurekan strain partitioning and decoupling in central Spitsbergen, Svalbard - Koehl, Jean-Baptiste P. (Solid Earth, 2021)
The present study of field, petrological, exploration well, and seismic data describes backward-dipping duplexes comprised of phyllitic coal and bedding-parallel décollements and thrusts localized along lithological transitions in tectonically thickened Lower Devonian to lowermost Upper Devonian; uppermost Devonian–Mississippian; and uppermost Pennsylvanian–lowermost Permian sedimentary strata of the Wood Bay and/or Wijde Bay and/or Grey Hoek formations; of the Billefjorden Group; and of the Wordiekammen Formation, respectively. The study shows that these structures partially decoupled uppermost Devonian–Permian sedimentary rocks of the Billefjorden and Gipsdalen groups from Lower Devonian to lowermost Upper Devonian rocks of the Andrée Land Group and Mimerdalen Subgroup during early Cenozoic Eurekan deformation in central Spitsbergen. Eurekan strain decoupling along these structures explains differential deformation between Lower Devonian to lowermost Upper Devonian rocks of the Andrée Land Group and/or Mimerdalen Subgroup and overlying uppermost Devonian–Permian sedimentary strata of the Billefjorden and Gipsdalen groups in central–northern Spitsbergen without requiring an episode of (Ellesmerian) contraction in the Late Devonian. Potential formation mechanisms for bedding-parallel décollements and thrusts include shortcut faulting and/or formation as a roof décollement in a fault-bend hanging wall (or ramp) anticline, as an imbricate fan, as an antiformal thrust stack, and/or as fault-propagation folds over reactivated or overprinted basement-seated faults. The interpretation of seismic data in Reindalspasset indicates that Devonian sedimentary rocks of the Andrée Land Group and Mimerdalen Subgroup might be preserved east of the Billefjorden Fault Zone, suggesting that the Billefjorden Fault Zone did not accommodate reverse movement in the Late Devonian. Hence, the thrusting of Proterozoic basement rocks over Lower Devonian sedimentary rocks along the Balliolbreen Fault and fold structures within strata of ...